Properties of laminated veneer lumber produced from small diameter rubber logs - Khoo, Pui San (2021)
Wood manufacturers have shifted their focus from natural to plantation forest resources such as rubberwood when the supply of large-sized logs from natural forests has diminished. However, with the further implementation of higher planting density and modern tapping method in Rubber Forest Plantation (RFP) in the past 20 years, rubber trees are harvested in younger age and are much smaller in diameter compared to the conventional planting and tapping method applied years back. The development of the spindleless lathe has made it possible to produce veneer from small-diameter plantation logs efficiently. Due to the fact that there are limited opportunities for changing the spindleless lathe settings, the processing parameters of laminated veneer lumber (LVL) has to be altered in a way that suits the unique quality of veneers produced from small diameter rubber log using spindleless lathe. Thus, the main objective of this study was to evaluate the physical and mechanical properties of LVL produced from small diameter rubber logs. Rubber trees (15 years old) with no economic value were selected from the RISDA forest plantation at Sungai Siput, Perak. These logs have smaller diameter (15 to 18 cm) compared to rubber logs that are normally harvested at an older age of 30 years old. In the preliminary study, the density distribution and fibre morphology of small diameter rubber trees were determined. Results shown the density of rubberwood varies across the cross section of rubber tree. Three veneer thicknesses of 1 mm, 2 mm and 3 mm were peeled from the outer to the inner radial of the log and the veneer quality was evaluated. The veneer recovery ranging from 62.56 to 65.36 %, and are classified as structural veneers C-grade, D-grade and E-grade. The surface of thinner veneer is smoother, with a lower lathe check depth but a higher lathe check frequency. Thick veneer was under thickness, has a rougher surface, with a deeper but lower lathe check frequency. Bonding performance of veneer on three different thicknesses was assessed by making them into three-ply LVL and pressing them at three different temperatures. ANOVA shows the bonding performance of 2 mm-thick veneer pressed with 120˚C has the highest gluebond shear strength of 5.91 MPa and lowest percentage of water absorption after two and 24-hours immersion. Two mm thick veneers were then selected in the fabrication of 12 mm-thick rubberwood LVL. The physical and mechanical properties were conducted according to ASTM D4442-07, ASTM D2395-14, ASTM D1037-12, ASTM D5456-10 and ASTM D906-11. Optimization of the processing parameters was further evaluated with four specific pressing pressures and three glue spread rates. Rubberwood LVL made from 2 mm veneer thickness with 120˚C pressing temperature, 200 g/m² glue spread rate and 9 kgf/cm² specific pressing pressure exhibit the highest mechanical properties of; 91.05 MPa for MOR in flatwise direction, 11189.55 MPa for MOE in flatwise direction, 50.23 MPa for compressive strength parallel to the longitudinal axis and 6.46 MPa for gluebond shear strength. Therefore, rubberwood LVL produced from small diameter rubber logs can be utilized for construction purposes such as roof or floor trusses.